(untitled) (International Journal of Engineering and Computer Science, 2014)
A wireless sensor network (WSN) consists of spatially distributed autonomous sensors to monitor physical or environmental conditions. When we work on a distributed sensor network then to control the communication over the network, some controller nodes are defined at various points over the network. These controller nodes are used to improve the effectiveness of the network by performing the routing as well as to identify the reliable communicating next node. This controller node is called the leader node that reduces the network communication and improves the network life. The election of the leader node is itself a challenging task and it affects the network reliability. In this paper, a multi parametric route tracing based approach is suggested to define a leader node in such a way so that the network life can be improved.